2022
DOI: 10.1177/01640275221126100
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Negative Aging StereotypesviaEducational Intervention in Older People: A Randomized Controlled Study

Abstract: Anti-ageism interventions traditionally target younger individuals. We analyzed the effect of an educational intervention that combined an infusion of aging content with videos to reduce negative stereotypes toward aging in a randomized controlled study of 56 community-dwelling older adults. The experimental group received a single one-hour information session and video viewing on ageism; the control group viewed 1 hour of videos unrelated to ageism. Repeated-measures ANOVA indicated that the experimental grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Furthermore, our effect sizes were notably very large, relative to what was achieved by Doncel-García et al (2023). That the effect sizes within our current study were comparable to the change resulting from an intervention designed to systematically refute the items used to measure change is promising.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Furthermore, our effect sizes were notably very large, relative to what was achieved by Doncel-García et al (2023). That the effect sizes within our current study were comparable to the change resulting from an intervention designed to systematically refute the items used to measure change is promising.…”
Section: Discussionsupporting
confidence: 48%
“…Other interventions focused solely on self-perceptions of aging found small effect sizes (Beyer et al, 2019), or no difference of self-perceptions of aging across experimental conditions (Menkin et al, 2022). Intervention outcomes pertaining to the outward manifestation of internalized ageism have been mixed, with research finding no impact (Lester & Murrell, 2022), small effects (Wolff et al, 2017), and in one case, large effects (Doncel-García et al, 2023). Doncel-García et al (2023) found large reductions in the endorsement of aging stereotypes.…”
Section: Effectiveness Of a Process Based Intervention In Decreasing ...mentioning
confidence: 99%
See 1 more Smart Citation